COMMUNICATION STRATEGIES USED BY SOME SHOPKEEPERS IN GUNUNG KAWI TOURISM OBJECT TO COMMUNICATE WITH FOREIGN TOURISTS - ., Ida Bagus Putu Suryadiputra; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
The existence of an ancient temple complex called Gunung Kawi in Tampaksiring, Gianyar makes the tourists from many countries visit the place. It encourages the shopkeepers in that area to communicate intensively to the tourists. Sometimes they use communication strategies to help them communicate. This study investigates the types of the communication strategies used by some shopkeepers in Gunung Kawi tourism object in communicating with foreign tourists, the type of communication strategies used most frequently by some shopkeepers and their reasons in applying communication strategies to communicate with foreign tourists. Two main methods used in this study were observation and interview. Five shopkeepers were observed. The findings of this study show that the shopkeepers used eight type of communication strategy namely approximation, circumlocution, clarification request, comprehension check, language switching, paralanguage, topic avoidance, and using pictures or objects. Paralanguage was the communication strategy which was used most frequently. Two main reasons why they applied communication strategies were found. They were to run the communication well and effectively, and to avoid misunderstanding during the communication process.Kata Kunci : Communication Strategies, Shopkeeper Keberadaan kompleks wisata pura Gunung Kawi di Tampaksiring, Gianyar menyebabkan banyaknya kunjungan wisata dari berbagai negara. Hal tersebut menyebabkan para pedagang cinderamata di tempat tersebut terbiasa berkomunikasi dengan para turis asing. Terkadang, mereka menggunakan strategi komunikasi untuk mempermudah komunikasi mereka. Penelitian ini membahas tentang tipe-tipe strategi komunikasi yang digunakan oleh para pedagang di tempat tersebut ketika berkomunikasi dengan turis asing, tipe strategi komunikasi yang paling sering digunakan ketika berkomunikasi dengan turis asing, dan alasan para pedagang tersebut menggunakan strategi komunikasi ketika berkomunikasi dengan turis asing. Metode yang digunakan dalam penelitian ini adalah observasi dan interview dimana lima pedagang diobservasi. Hasil dari penelitian ini menunjukkan bahwa para pedagang yang diobservasi menggunakan delapan jenis strategi komunikasi yaitu approximation, circumlocution, clarification request, comprehension check, language switching, paralanguage, topic avoidance, and using pictures or objects. Paralanguage adalah tipe strategi komunikasi yang paling sering digunakan. Ada dua alasan utama tentang penggunaan strategi komunikasi yang dikemukakan oleh para pedagang yaitu untuk membuat komunikasi berjalan lancar dan efektif, serta untuk menghindari kesalahpahaman selama komunikasi berlangsung.keyword : Strategi Komunikasi, Pedagang